(untitled) (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2024)
this article deals with the language and conversation as well as the difference between spoken and written form of speech. In addition, author gives several possible notions from prominent linguists who contributed to find solution of the issue.